Integrated modelling for coastal alluvium aquifer at Kg. Tekek, Tioman Island - Liew, Kuet Fah (2006)
Sufficient water supply plays an important role in busting the continuous growth of tourism industry for an island. Tioman Island as one of the well-known marine tourism attraction in Malaysia still highly relies on the limited surface water source to supply water for the local residents and tourists. Thus, exploration for the groundwater source is essential as an supplement for the existing water supply system to cater for the increasing water demand in the future. Utilization of surface water and groundwater will prevent the total reliance on a single resource which avoids the water scarcity problem during drought seasons and also occurrence of groundwater overdraft. Groundwater modellings in this study are developed with MODFLOW2000 based on the available data to determine the hydraulic heads and drawdowns of groundwater due to different pumping rates and saline intrusion effects are simulated with the SEAWAT2000 model. The linear optimization problem is solved with GAMS to maximize the rate of pumping for groundwater to fulfill the quantity and quality requirements. The aquifer system would be capable to support withdrawal of groundwater up to 5.8 MLD and cater for water demand till year 2015. The hydraulic drawdown has greater influence for the optimization of pumping rate compared to saline intrusion effects. With additional supply from surface water source of 4 MLD, the combination system could cater for the water demand up to year 2025.